Clinicoetiology profile of neonatal seizures in tertiary care Level II neonatal intensive care unit - Bagla, Jyoti; Garg, Hariom; Gulati, R K; Gupta, P P (Indian Journal of Child Health, 2017)
Objective: To study the incidence, etiology, and pattern of neonatal seizures and its relationship with age of onset, gestation, and other obstetrical factors. Design: Prospective observational descriptive study. Setting: Level II neonatal intensive care unit of a Government Medical College Hospital. Participants: 72 neonates with neonatal seizures admitted at our hospital and developed seizures before 28 days of life. Results: The incidence of neonatal seizure was 11.93/1000 live births. The seizures were more common in male babies and in term newborns (72%). Half of the babies with neonatal seizures were low birth weight (LBW), but seizures were significantly more in appropriate for gestation age in comparisons to small for gestation age babies. Seizure frequency was not different in babies born intramural or extramural and also in deliveries conducted by doctors, nurses, or TBAs. Subtle seizures were the most common pattern observed in both term and preterm newborns (38.9%) followed by generalized tonic (22.3%). Birth asphyxia was most common etiology followed by meningitis in our study. Conclusion: Birth asphyxia meningitis, hypocalcemia, and hypoglycemia are common etiology, and the majority present within the first 72 h of life. All the high-risk newborns (asphyxiated or LBW) should be monitored at least 72 h of birth for seizures.